MOTIVASI BELAJAR SISWA - Al Kautsar Azhari; Siti Muhibah; Deasy Yunika Khairun (STKIP Subang, 2025)
Learning motivation plays a crucial role in determining students’ engagement and academic persistence, particularly at the junior secondary level where adolescents experience significant cognitive, emotional, and social transitions. This study aims to describe and analyze the learning motivation of eighth-grade students at SMP Negeri 1 Ciruas in the 2025/2026 academic year, along with the factors influencing it. A descriptive qualitative approach was employed to capture students’ subjective experiences and contextual learning dynamics. Data were collected through in-depth interviews, participatory observation, and documentation involving three eighth-grade students, a guidance and counseling teacher, and the vice principal for curriculum affairs. Data analysis followed Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing, supported by source triangulation to ensure credibility. The findings indicate that students’ learning motivation ranges from moderate to high and is shaped by both internal and external factors. Internally, motivation is driven by students’ desire to succeed, self-confidence, learning awareness, and future aspirations. Externally, supportive teacher–student relationships, positive peer interactions, recognition through verbal appreciation, engaging learning activities, and a safe, well-facilitated school environment contribute significantly to sustaining motivation. The role of guidance and counseling services is pivotal in strengthening intrinsic motivation and helping students connect present learning with future goals. Overall, students’ learning motivation emerges as a dynamic interaction between individual agency and the school environment, highlighting the importance of a holistic and human-centered educational approach.